2017
DOI: 10.3171/2016.9.jns161629
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic radiographic response resulting in cerebrospinal fluid rhinorrhea associated with sunitinib therapy in recurrent atypical meningioma: case report

Abstract: Sunitinib is a multiple tyrosine kinase inhibitor with antiangiogenic, cytostatic, and antimigratory activity for meningiomas. A recent clinical trial of sunitinib for treatment of recurrent Grade II and III meningiomas suggested potential efficacy in this population, but only 2 patients exhibited significant radiographic response with tumor volume reduction. The authors illustrate another such case and discuss a complication related to this dramatic tumor volume reduction in aggressive skull base meningiomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…CSF rhinorrhea has been described following non-surgical treatment (medical management/SBRT) of pituitary tumors and meningiomas. [1,2] To the best of our knowledge, there is a single published case report of CSF rhinorrhea occurring in metastatic lung cancer (EGFR mutated LUAC) after erlotinib treatment. [3] Although the exact mechanism remains unclear, the possibility entertained in our case was something akin to benign intracranial hypertension (subclinical raised ICT), as there was empty sella sign with flattening of posterior globe and perineural enhancement of the optic nerves on imaging, and she had developed CSF rhinorrhea after 12 months of treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…CSF rhinorrhea has been described following non-surgical treatment (medical management/SBRT) of pituitary tumors and meningiomas. [1,2] To the best of our knowledge, there is a single published case report of CSF rhinorrhea occurring in metastatic lung cancer (EGFR mutated LUAC) after erlotinib treatment. [3] Although the exact mechanism remains unclear, the possibility entertained in our case was something akin to benign intracranial hypertension (subclinical raised ICT), as there was empty sella sign with flattening of posterior globe and perineural enhancement of the optic nerves on imaging, and she had developed CSF rhinorrhea after 12 months of treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of platelet-derived growth factor receptor (PDGFR)-mediated signaling by RTK inhibitors sorafenib and regorafenib inhibits the proliferation of IOMM-Lee MGM cells, as well as the growth of experimental IOMM-Lee MGM tumors in vivo in mice inoculated with IOMM-Lee MGM cells into the subarachnoidal space, through PDGFR downregulation and inhibition of expression and phosphorylation of p44/42 ERK [ 25 ]. A few cases of tumor responses to the multiple RTK inhibitor sunitinib have been reported in patients with grade II and III MGMs [ 26 , 27 ]. The subjects in one trial were patients with recurrent or progressive atypical and anaplastic MGM tumors, heavily pretreated and refractory to treatments.…”
Section: Molecular Changes and Novel Molecularly Targeted Therapeutic Strategiesmentioning
confidence: 99%
“…Inhibition of PDGF receptor (PDGFR)-mediated signaling by RTK inhibitors sorafenib and regorafenib inhibits the growth of experimental MGM in vitro and in vivo, thought PDGFR downregulation and inhibition of p44/42 ERK [24]. A few cases of tumor responses to the multiple RTK inhibitor sunitinib have been reported in patients with grade II and III MGMs [25,26]. Patients with recurrent MGM tumors refractory to surgery and radiation treated with the oral multi-RTK inhibitor PTK787/ZK 222584 (PTK787) showed that grade II patients had a progression free survival-6 of 64.3 %, a median progression free survival of 6.5 months, and an overall survival of 26.0 months; grade III patients had a progression free survival-6 of 37.5 %, median progression free survival of 3.6 months, and overall survival of 23 months [27].…”
Section: Molecular Changes and Novel Molecularly-targeted Therapeutic Strategiesmentioning
confidence: 99%